2013
DOI: 10.1089/fpd.2012.1307
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Foodborne Illness Among Attendees of a Wedding Reception in Wisconsin Likely Caused byArcobacter butzleri

Abstract: The results of this investigation suggest that A. butzleri should be considered an agent that can cause outbreaks of foodborne illness. Rigorous investigation of outbreaks of undetermined etiology is valuable for incrementally increasing our understanding of emerging agents causing foodborne illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 34 publications
0
32
0
5
Order By: Relevance
“…Recent evidence suggests that Arcobacter spp., especially A. butzleri and A. cryaerophilus, may be involved in human enteric diseases (Tee et al 1988, Vandamme et al 1992a, Lappi et al 2013. Occasionally these species have also been found in cases of human extraintestinal diseases (Hsueh et al 1997, Lau et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that Arcobacter spp., especially A. butzleri and A. cryaerophilus, may be involved in human enteric diseases (Tee et al 1988, Vandamme et al 1992a, Lappi et al 2013. Occasionally these species have also been found in cases of human extraintestinal diseases (Hsueh et al 1997, Lau et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…However, one report of a putative Arcobacter outbreak at a wedding reception suggested that symptoms may be observed as little as 6 hours and as long as three days post ingestion (Lappi et al, 2013). The mean incubation period for this outbreak was approximately 31 hours.…”
Section: Incubation Periodmentioning
confidence: 95%
“…Like chicken, the risk of infection is due to improper hygiene after handing of raw meat and/or consumption of undercooked meat. A foodborne outbreak in a wedding reception was associated with consumption of broasted chicken contaminated with Arcobacter, demonstrating direct linkage between poultry consumption and human GI disease (Lappi et al, 2013). As geese and ducks are waterfowl, they may represent a significant source of Arcobacter contamination in still bodies of fresh water.…”
Section: Poultrymentioning
confidence: 99%
“…The successive timing of the cases suggested person-to-person contact (Vandamme et al 1992). Lappi et al (2013) reported on an outbreak of foodborne illness among attendees at a wedding reception. Forty-seven patients and 43 healthy attendees were included in a case-control study.…”
Section: Clinical Relevancementioning
confidence: 99%